Session: Authors Rights and Other Legal Problems - Vranić-Ignjačević, Marija (Infotheca - Journal for Digital Humanities, 2024)
This session took part in the frames of IFLA CORNER. From its title it can be concluded that the given presentations where not in the main stream of professional library subjects.